A novel instrument of cognitive and social congruence within peer-assisted learning in medical training: construction of a questionnaire by factor analyses - Festl-Wietek, Teresa; Erschens, Rebecca; Nikendei, Christoph; Giel, Katrin; Junne, Florian; Zipfel, Stephan; Herrmann-Werner, Anne (BMC medical education, 2020)
Peer-assisted learning is effective due to cognitive and social congruence. Cognitive congruence is created by sharing a similar knowledge base between students and student tutors. Social congruence is defined as having similar social roles. A questionnaire of these concepts was newly constructed, and this study explored the factor analysis of the instrument.